Utilization of Carboxymethyl Cellulose from Durian Rind Agricultural Waste to Improve Physical Properties and Stability of Rice Starch-Based Film - Rungsiri Suriyatem (2019)
© 2018, Springer Science+Business Media, LLC, part of Springer Nature. The aim of this work was to enhance the mechanical properties and durability of rice starch (RS)-based film by incorporating carboxymethyl cellulose derived from durian rind (CMCd). Mechanical and thermal properties, swellability, permeability (oxygen and water), color, opacity, thermal stability and biodegradability of the films were determined. Fourier transform infrared (FTIR) and X-ray diffraction techniques were used to demonstrate interactions between films components and their compatibility. Incorporation of the CMCd into the RS-based film caused a decreased lightness, redness and whiteness index but increased transparency, yellowness and total color difference among the blended films and RS film. An increase of tensile strength for all RS/CMCd blended films without change of elongation at break was also observed. Decomposition temperature of the blended films was lower than the RS film while thermal stability was higher. All blended films provided higher equilibrium swelling ratio than the RS film. Incorporation of CMCd did not influence the water vapor and oxygen permeability of the blended films. The FTIR analysis confirmed the interactions between the –OH groups of RS and the COO– groups of CMCd. Scaning electron microscopy analysis represented homogenious cross-sectional surface of all films. The RS, CMCd and RS/CMCd 50:50 films were tested in simulated compost environmental conditions to study their biodegradability. The RS/CMCd 50:50 films showed lower evolved CO 2 and %mineralization than the RS film.